Microstructural geochronology : planetary records down to atom scale - Desmond E.Moser (Geophysical monograph, 2018)
"Geochronology techniques enable the study of geological evolution and environmental change over time. This volume integrates two aspects of geochronology: one based on classical methods of orientation and spatial patterns, and the other on ratios of radioactive isotopes and their decay products. The chapters illustrate how material science techniques are taking this field to the atomic scale, enabling us to image the chemical and structural record of mineral lattice growth and deformation, and sometimes the patterns of radioactive parent and daughter atoms themselves, to generate a microstructural geochronology from some of the most resilient materials in the solar system. Volume highlights include: first compilation of research focusing on the crystal structure, material properties, and chemical zoning of the geochronology mineral archive down to nanoscale; novel comparisons of mineral time archives from different rocky planets and asteroids and their shock metamorphic histories; and fundamentals on how to reconstruct and date radiogenic isotope distributions using atom probe tomography. Microstructural Geochronology will be a valuable resource for graduate students, academics, and researchers in the fields of petrology, geochronology, mineralogy, geochemistry, planetary geology, astrobiology, chemistry, and material science. It will also appeal to philosophers and historians of science from other disciplines" --